MARINE RESOURCE GOVERNANCE: A SYSTEMATIC LITERATURE REVIEW OF POLICY TRENDS AND COLLABORATIVE MANAGEMENT APPROACHES - Muhammad Luthfi Siraj (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
This study aimed to analyze the development of marine resource governance research through a Systematic Literature Review (SLR) based on bibliometric analysis. The study examined publication trends, major contributors, geographical distribution, and the intellectual structure of the field. Data were collected from the Scopus database using keywords related to marine resource governance and ocean governance. An initial search identified 1,266 documents, which were filtered to 473 articles published between 2016 and 2023. Data analysis employed Scopus Analyze Search Results and VOSviewer through co-occurrence, overlay, and density visualizations. The findings indicate a significant increase in publication output and reveal that marine resource governance has become an increasingly interdisciplinary field dominated by Environmental Science and Social Sciences. The United States, Australia, and the United Kingdom emerged as the leading contributors. Research themes have shifted toward climate change, biodiversity conservation, blue economy, and collaborative governance approaches, highlighting the growing importance of adaptive and participatory ocean governance